Bee conservation in Sub-Saharan Africa and Madagascar: diversity, status and threats - (:unkn) unknown (My University, 2009)
Sub-Saharan Africa and Madagascar contain a wealth of bee diversity, with particularly high levels of endemicity in Madagascar. Although Africa contains seven biodiversity hotspots, the bee fauna appears rather moderate given the size of the continent. This could be due to various factors, an important one being the dearth of bee taxonomists working in Africa and difficulties in carrying out research in many regions. Anecdotal observations suggest a very large number of undescribed bee species. A number of serious threats to this diversity exist, especially habitat destruction and degradation. Bee diversity in these regions is likely to be important for both agriculture and indigenous ecosystems, but is under-appreciated. Reliance on conserved areas such as National Parks will not be sufficient to preserve bee diversity in Africa and Madagascar; changes to land use practices and development of industries that facilitate conservation, such as ecotourism, will be essential. There is also a strong need to build regional expertise and infrastructure that can be used for documenting bee diversity, identifying the most urgent conservation issues, and implementing conservation strategies. Support from developed countries and international funding agencies is needed for this.
Keywords: African Research